Is gene editing natural and does it matter? A qualitative analysis of citizen-consumers’ and farmers’ views on the use of new genomic techniques in plants - Huttunen, Katriina; Artell, Janne; Heinola, Katriina; Pouta, Eija; Schulman, Alan H.; Tienhaara, Annika; Viitala, Sirja; Vainio, Annukka (Springer Nature, 2026)
This study examines the notions of ‘naturalness’ in Finnish citizen-consumers’ and farmers’ perspectives, through ten focus group discussions, on genetic modification (GM) and new genomic techniques (NGTs) in plant breeding, amidst the current European Union (EU) legislative changes. In this context, the study shows that citizen-consumers’ views on GM plants and NGTs are significantly associated with different notions of ‘naturalness’ that are closely entangled with each other. Some citizen-consumers consider any human intervention as unnatural and unacceptable, while others are open to NGTs if they resemble natural processes or traditional breeding methods. Those who do not explicitly make use of the notion of naturalness are the most open towards all genetic techniques. However, consideration of the use purpose of NGTs can shift views of citizen-consumers. Farmers, in contrast, focus less on naturalness and more on the practical and economic implications of NGTs. Organic farmers expressed concerns about being excluded from the benefits of NGTs. Despite some caution towards transgenesis, most farmers were open to using NGTs due to the pressing challenges they face, such as climate change and economic pressures. The study concludes that different understandings of (un)naturalness are inextricably linked and continuously shape each other, rather than existing independently. This dynamic interdependence, in turn, underlie shifting views of NGTs in different contexts.
Keywords: new genomic techniques; naturalness; genomics; public perception